2005
DOI: 10.1261/rna.2930805
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin is not a functional mimic of the 7-methyl guanosine mRNA cap

Abstract: Ribavirin is a guanosine ribonucleoside analog that displays broad-spectrum anti-viral activity and is currently used for the treatment of some viral infections. Ribavirin has recently been proposed to also be a mimic of the 7-methyl guanosine cap found at the 5 0 end of mRNAs. To obtain supporting functional data for this hypothesis, we assessed the ability of ribavirin triphosphate to interfere with the interaction between eIF4E and 7-methyl guanosine capped mRNA. In chemical cross-linking assays, cap-affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 45 publications
1
47
0
Order By: Relevance
“…After this work had been accepted for publication, another study (Yan et al 2005) reported similar observations.…”
Section: Note Added In Proofsupporting
confidence: 56%
“…After this work had been accepted for publication, another study (Yan et al 2005) reported similar observations.…”
Section: Note Added In Proofsupporting
confidence: 56%
“…In recent issues of RNA, Yan et al (2005) and Westman et al (2005) present findings that dispute this conclusion. Their results are twofold: that ribavirin does not bind to recombinant eIF4E in vitro, and that ribavirin does not inhibit cap-dependent translation of exogenous mRNAs in extracts prepared from cells.…”
mentioning
confidence: 95%
“…With this in mind, we reproduced our original affinity chromatography experiment using an independent operator and new reagents side by side with the experiment of Yan et al (2005). We reproduced experimental conditions as published by us (0.3 M NaCl, 0.1 M sodium phosphate, 0.1% Nonidet P-40, 10 mM BSA at pH 7.5, room temperature), and those described by Yan et al (2005) GTP itself (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence and effects of such interactions have been presumed in the interpretation of many biological functions of the 7-methylguanosine, other alkylated nucleic acid bases and their nucleotide derivatives. One example is the eukaryotic mRNA with a special CAP structure (see [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] and the references therein) (the 5'cap is found on the end of mRNA molecule and consists of a guanine nucleotide connected to the mRNA via an unusual 5' to 5' triphosphate linkage). This guanosine is methylated on the 7 position directly after capping in vitro by a methyl transferase.…”
Section: Introductionmentioning
confidence: 99%